Development of a mouse computational model for MCNPx based on Digimouse (r) images and dosimetric assays - Bruno Melo Mendes; Iassudara Garcia de Almeida; Bruno Machado Trindade; Telma Cristina Ferreira Fonseca; Tarcísio Passos Ribeiro de Campos (Universidade de São Paulo, 2017)
ABSTRACT The aim of this study was to create and test a new mice 3D-voxel phantom named DM_BRA for mice and human first-estimation radiopharmaceutical dosimetry. Previously, the article reviews the state-of-art in animal model development. Images from Digimouse CT database were used in the segmentation and on the generation of the voxelized phantom. Simulations for validation of the DM_BRA model was performed at 0.015, 0.1, 0.5, 1 and 4 MeV photons with heart-source. Specific Absorbed Fractions (SAF) data were compared with literature data. The organ masses of DM_BRA correlated well with existing models based on the same dataset; however, few small organ masses hold significant variations. The SAF data in most simulated cases were statistically equal to a significant level of 0.01 to the reference data.